RECORDS MANAGEMENT SYSTEM AT THE SOUTH SULAWESI PROVINCIAL EDUCATIONAL QUALITY ASSURANCE INSTITUTION - Muh. Ersyad Indra Praja; Muhammad Luthfi Siraj; Darnianty Asis; Suprianto Suprianto (Universitas Cahaya Prima, 2026)
Effective records management has become a strategic component of organizational governance, particularly in public institutions responsible for ensuring accountability, transparency, and efficient service delivery. This study aimed to evaluate the effectiveness of the records management system implemented at the South Sulawesi Provincial Educational Quality Assurance Institution. A quantitative descriptive approach was employed using a questionnaire distributed to 43 employees selected through proportionate stratified random sampling from a population of 173 employees. Data were analyzed using descriptive percentage analysis based on five dimensions of the records life cycle: records creation, records handling and control, records utilization, records maintenance, and records disposition and disposal. The findings revealed that the overall effectiveness of the records management system reached 89.82%, indicating that it was implemented effectively. Among the five dimensions, records creation achieved the highest effectiveness score (95.51%), followed by records utilization (91.67%), records maintenance (88.60%), records handling and control (87.79%), and records disposition and disposal (84.19%). Although all dimensions were categorized as effective, improvements are still required in archival infrastructure, records disposition procedures, and digital records management to enhance long-term efficiency and institutional accountability. This study contributes to the literature by providing empirical evidence on records management practices in educational quality assurance institutions, a context that has received limited attention in previous research. The findings highlight the importance of adopting comprehensive records management practices aligned with the records life-cycle framework to strengthen governance and support evidence-based decision-making in public organizations.